Unpacking the Meaning of a Standards-based Education System - Manjunath, Madhumati; Banerjee, Shilpi (Voices of Teachers and Teacher Educators, 2022)
Countries all over the world have increasingly been adopting standards-based reforms in their school systems. A proliferation of concepts and terms related to the concepts of standards-based education systems has followed as well. Thus, there is a need for papers that help clarify concepts and terms related to standards-based education systems. This paper provides an overview of the features of standards-based education systems, with a brief discussion on standards-based reform in India. More importantly, it clarifies the meanings of terms related to standards-based curricula—aims, competencies, goals, learning outcomes, and instructional objectives—with examples specifically related to the Indian context. The paper discusses some caveats associated with standards-based education systems and concludes with suggestions for improvement and implementation.